Negative Autoregulation of GTF2IRD1 in Williams-Beuren Syndrome via a Novel DNA Binding Mechanism - Palmer, Stephen J. (American Society for Biochemistry and Molecular Biology, 2010)
The GTF2IRD1 gene is of principal interest to the study of Williams-Beuren syndrome (WBS). This neurodevelopmental disorder results from the hemizygous deletion of a region of chromosome 7q11.23 containing 28 genes including GTF2IRD1. WBS is thought to be caused by haploinsufficiency of certain dosage-sensitive genes within the deleted region, and the feature of supravalvular aortic stenosis (SVAS) has been attributed to reduced elastin caused by deletion of ELN. Human genetic mapping data have implicated two related genes GTF2IRD1 and GTF2I in the cause of some the key features of WBS, including craniofacial dysmorphology, hypersociability, and visuospatial deficits. Mice with mutations of the Gtf2ird1 allele show evidence of craniofacial abnormalities and behavioral changes. Here we show the existence of a negative autoregulatory mechanism that controls the level of GTF2IRD1 transcription via direct binding of the GTF2IRD1 protein to a highly conserved region of the GTF2IRD1 promoter containing an array of three binding sites. The affinity for this protein-DNA interaction is critically dependent upon multiple interactions between separate domains of the protein and at least two of the DNA binding sites. This autoregulatory mechanism leads to dosage compensation of GTF2IRD1 transcription in WBS patients. The GTF2IRD1 promoter represents the first established in vivo gene target of the GTF2IRD1 protein, and we use it to model its DNA interaction capabilities.